ANALISIS PERBEDAAN PERSEPSI MAHASISWA AKUNTANSI YANG MEMPENGARUHI PILIHAN KARIR - Pasaribu, Hiras; Kusumawardhani, Indra (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2013)
This study aims to determine the differences in perception between accountingstudents start the semester and final semester of the factors that influence careerchoices in terms of financial rewards, professional training, social values, the workenvironment, job security and the labor market and personality. The study wasconducted on 100 students in the first year of the study period and 100-yearstudents at the end of the study program at the Faculty of Economics of AccountingStudies UPN